THE TRANSLATION OF IMPLICIT COMPLIMENTS IN SUBTITLE OF BUMI MANUSIA: CROSS-CULTURAL PRAGMATICS - Damayanti, Alfira Andini; Sudarwati, Emy (Universitas Islam Sumatera Utara (UISU), 2024)
Implicit compliments were one of the speech acts forms, often found in high-context cultures such as Indonesia, in which implicitly attributed credit to someone other than the speaker, conveying admiration indirectly. The study aimed to provide a new perspective that not only contributed to the existing literature on cross-cultural pragmatics and translation studies, but also addressed the possible challenges posed by implicit compliments in movie translation in terms of Indonesian cultural context. The data for this study were collected by watching the movie “Bumi Manusia” on Netflix, observing both the original Indonesian dialogue and the English subtitles. Through the analysis, the study identified two main types of implicit compliments, those referring to achievements and those involving comparisons based on Boyle's (2000) framework. From the 28 data collected, the findings indicated that translators employed several translation procedures proposed by Newmark (1988), such as modulation, transposition, transference, and cultural equivalence to convey the meaning of implicit compliments. Furthermore, this study also highlighted the inherent challenges associated with the translation of implicit compliments, particularly in terms of cultural and linguistic aspects, including symbolic cultural meaning, language structure, and culturally specific terms.